LARGE SCALE YELLOW FEVER VACCINATION: PARTICIPATORY RATE AMONG HEALTH PROFESSIONAL TRAINEES AT MILDMAY INSTITUTE OF HEALTH SCIENCES, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Tubenawe, Martha; Nansereko, Hasifa; IMMACULATE , NAGGULU PROSPERIA; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Background Yellow fever remains a major public health issue in Uganda and other tropical regions. Health professions trainees are critical in preventing and controlling yellow fever outbreaks, but their vaccination status and knowledge about the disease were not well-documented. The study aimed to determine the prevalence of yellow fever vaccination and the knowledge of health professional trainees regarding yellow fever and its vaccination. Methodology A cross-sectional study was conducted among 40 health professional trainees at Mildmay Institute of Health Sciences. Data was collected using a structured questionnaire. Data was analyzed using descriptive statistics and cross-tabulation of the key characteristics using an Excel spreadsheet. Results were presented in tables, charts, and graphs to represent key findings and illustrate distributions, respectively. Results The results from the data collection showed yellow fever vaccination prevalence was 72.5% being vaccinated and 27.5% being unvaccinated, with males (91.7%) showing higher coverage than females (64.3%). Trainees aged 31-35 had 100% vaccination coverage, compared to 69.7% among those aged 18-25. Socio-economic status also influenced vaccination rates, with trainees from high-income backgrounds (83.3%) more likely to be vaccinated than those from middle (69.0%). Knowledge about yellow fever transmission, symptoms, and vaccination benefits was high among most respondents. Conclusion Although vaccination rates were generally strong, younger trainees and females showed lower coverage. Recommendation There should be targeted vaccination initiatives for these groups and integration of vaccination services with educational programs within training institutions.